Quantitative real-time PCR based evaluation and validation of reference genes in Gossypium arboreum - P, RAGHAVENDRA K; KUMAR, RAKESH; DAS, JOY; B, SANTOSH H; MORE, SACHIN A; N, RAMAKRISHNA; CHAWLA, SHILPA G; KRANTHI, SANDHYA; KRANTHI, KESHAV RAJ (The Indian Journal of Agricultural Sciences, 2020)
Estimation of gene expression levels plays a crucial role in understanding the function of the target gene(s). Intersample variance in gene expression can be more precisely measured if transcripts levels are accurately normalized. Normalization is pre-requisite step prior to the determination of candidate gene expression by qPCR. In this study conducted at ICAR-Central Institute for Cotton Research, Nagpur during 2015–16, six candidate reference genes, viz. actin4 (ACT4), actin7(ACT7), RNA Helicase (RNAH), Serine/threonine-protein phosphatase PP2A-1(PP2A1), ubiquitin7 (UBQ7) and α tubulin (αTUB) were systematically analysed for their expression patterns in different tissues pertaining to three development stages of cotton namely seedling, early reproductive and fiber development. The study has identified actin-4/actin-7/ubiquitin-7 as the most ideal reference genes for fiber development stages whereas actin-4/ ubiquitin-7 and actin-7/RNA helicases for seedling and early reproductive development stages, respectively. Validation of identified reference genes for relative expression analysis of Gacobl9, a COBRA-like protein, demonstrated their usefulness in qPCR analysis in Gossypium arboreum.